Quality of Life in Patients with Pityriasis Rosea is Associated with Rash Severity - Hapa, Aslı; Yıldırım, Elif; Aksoy, Berna; Mutlu, Emine (Cerrahpaşa Medical Journal, 2020)
Objective: Few investigations have assessed quality of life (QOL) in pityriasis rosea (PR) patients. Our objective is to determine if QOL in PR patients is influenced. Methods: Eighty-five patients with PR and 90 healthy controls were enrolled into the study. Each participant completed the Dermatology Life Quality Index (DLQI). The severity of PR and pruritus was assessed using the Pityriasis Rosea Severity Score (PRSS) and a visual analog scale (VAS), respectively. Results: Total DLQI scores of the 85 patients with PR (median: 6; range 1- 28) were signiﬁcantly higher than those of the 90 controls (median, 1; range 0-8). The DLQI scores of PR patients decreased significantly following treatment (median, 2; range 0- 20). The median PRSS score of 47 PR patients who attended follow-ups, was 24 before treatment (range 2- 48) and significantly decreased to 9 (range 0- 42) after treatment. There was a strong positive correlation between the PRSS scores and DLQI scores of patients before (r: 0.359; p: 0.000) and after (r: 0.628; p: 0.000) treatment. Conclusion: The DLQI of patients with PR decreases significantly after treatment and QOL is correlated with rash severity, therefore, we recommend treating this self-limiting condition, especially in patients presenting with severe disease. Cite this article as: Hapa A, Yıldırım E, Aksoy B, Mutlu E. Quality of Life in Patients with Pityriasis Rosea is Associated with Rash Severity. Cerrahpaşa Medical Journal 2020; 44(1): 21-26.